Pengaruh Channel Youtube Beauty Vlogger Tasya Farasya terhadap Minat Beli Produk Skintific Mahasiswa Fakultas Ushuluddin, Adab dan Dakwah Iain Parepare - Herviani, Herviani; Ramli; Nur Salwiyani Gani (Journal of Media and Communication Studies, 2024)
This skipsi discusses "The Influence of Beauty Vlogger Tasya Farasya's Youtube Channel on the Interest in Buying Skintific Products of Ushuluddin, Adab and Da'wah Faculty Students at IAIN Parepare". This research aims to determine and describe the magnitude of the influence of Beauty Vlogger Tasya Farasya's source credibility and content on interest in purchasing Skintific products. This research uses a quantitative approach where the data is in the form of numbers which are processed using descriptive analysis and statistical analysis with multiple linear regression, using the Slovin formula with 10% precision, namely with a sample of 94 female students who are considered to be representative of the population. Source credibility theory is the theory used in this research. According to this theory, people tend to trust and accept messages more from those who have expertise in their field. Based on the research results, it can be concluded that the results of hypothesis testing using the regression test obtained (R Square) for the source credibility variable on purchase interest of 0.193 (19.3%). It can be concluded that the magnitude of the influence between source credibility on buying interest is 19.3% then (R Square) the content variable on buying interest is 0.436 (43.6%). So it can be concluded that the magnitude of the influence of content on purchasing interest is 43.6%.